Minimal nonsupersolvable and minimum nonnilpotent groups and their role in the study of the structure of finite groups - Semenchuk, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the influence of minimal nonsupersoluble subgroups and minimal nonnilpotent subgroups (Schmidt subgroups) of a group on its structure.